2017
DOI: 10.1093/dote/dow027
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of the T2 substage in patients with esophageal squamous cell carcinoma

Abstract: The invasion of the muscularis propria is defined as T2 stage in esophageal squamous cell carcinoma. Evidence is lacking regarding whether the T2 substage based on anatomy may serve as a prognostic indicator. This study aims to confirm the prognostic value of the T2 substage. The clinicopathological characteristics of 120 patients who had pathologically verified T2 tumors between 2006 and 2011 at the Tianjin Medical University Cancer Institute and Hospital were retrospectively studied. Based on the invasion de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 20 publications
3
8
0
Order By: Relevance
“…Nevertheless, we could not determine whether there were differences in general characteristics between patients with T2 circular and T2 longitudinal ESCC in this study. Similarly, a study of 120 patients by Duan et al [9] also emphasized the poor prognosis of T2 longitudinal patients ( P < 0.001). However, the above studies were single‐center studies with relatively small sample populations, which might have led to inaccurate results.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…Nevertheless, we could not determine whether there were differences in general characteristics between patients with T2 circular and T2 longitudinal ESCC in this study. Similarly, a study of 120 patients by Duan et al [9] also emphasized the poor prognosis of T2 longitudinal patients ( P < 0.001). However, the above studies were single‐center studies with relatively small sample populations, which might have led to inaccurate results.…”
Section: Discussionmentioning
confidence: 84%
“…With increasing tumor invasion depth, patients with T2 ESCC have a greater risk of LNM, but this finding does not suggest that T2 ESCC should be subclassified. However, the association between LNM and the T2 substage in previous studies was positive, and patients with T2 longitudinal ESCC had a higher incidence of positive lymph nodes than patients with T2 circular ESCC (52.2% vs 30.8%, 37.2% vs 19.0%, P < 0.05) [8, 9]. This apparent difference might be due to the size of the sample population.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Two studies investigated tumour invasion depth into the muscularis propria as risk factor for LNM in pT2 squamous cell carcinoma 38,39 . Depth of invasion into the muscularis propria was classified as invasion into the outer longitudinal versus the inner circular muscle layer.…”
Section: Resultsmentioning
confidence: 99%
“…Two studies investigated tumour invasion depth into the muscularis propria as risk factor for LNM in pT2 squamous cell carcinoma. 38,39 Depth of invasion into the muscularis propria was classified as invasion into the outer longitudinal versus the inner circular muscle layer. Both Duan et al and Guo et al reported that pT2 tumours invading into the longitudinal layer were at an increased risk for LNM with OR 2.5 (95% CI: 1.0-6.2) and OR 2.5 (95% CI: 1.0-6.0), respectively (Supplementary Material Table 5).…”
Section: Depth Of Invasion In the Muscularis Propriamentioning
confidence: 99%